2015
DOI: 10.1007/s00330-015-3816-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative CT analysis of pulmonary ground-glass opacity nodules for distinguishing invasive adenocarcinoma from non-invasive or minimally invasive adenocarcinoma: the added value of using iodine mapping

Abstract: Quantitative analysis using DECT was used to distinguish invasive adenocarcinoma. Tumour mass and uniformity were independent predictors of invasive adenocarcinoma. Diagnostic performance was improved after adding iodine parameters to VNC parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(71 citation statements)
references
References 31 publications
2
69
0
Order By: Relevance
“…However, there are few previous researches assessing the amount of enhancement in pGGNs (14-16). Recently, Son et al (16) found that combining with texture analysis and DECT imaging, the heterogeneity within the tumors on the iodine-enhanced imaging was more obvious than virtual non-contrast (VNC) imaging, and could improve the power of diagnosing IA. However, texture analysis is a complicated and time-consuming analysis method, and is still not in common use now.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are few previous researches assessing the amount of enhancement in pGGNs (14-16). Recently, Son et al (16) found that combining with texture analysis and DECT imaging, the heterogeneity within the tumors on the iodine-enhanced imaging was more obvious than virtual non-contrast (VNC) imaging, and could improve the power of diagnosing IA. However, texture analysis is a complicated and time-consuming analysis method, and is still not in common use now.…”
Section: Discussionmentioning
confidence: 99%
“…Using iodine decomposition imaging of DECT, some researchers have observed enhancement of GGNs (14)(15)(16). Because iodine concentration (IC) would not be affected by air in lesions, it is considered to reflect blood volume better than CT number in GGNs (14).…”
Section: Original Articlementioning
confidence: 99%
“…Indeed, in some cases, GGO nodules have been associated with non-lepidic invasive adenocarcinoma. For those reasons, recent studies have been conducted to ascertain the predictive factors for the presence of invasive adenocarcinoma when GGO nodules are present (19)(20)(21). We defined GGO-predominant nodules as those with a C/T ratio <0.5 and solid-predominant nodules as those with a C/T ratio ≥0.5.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of chest computed tomography (CT) for lung cancer screening and ground glass opacity (GGO) detection has increased. The persistent presence of GGO nodules on CT usually suggests the presence of lung adenocarcinoma or a precancerous lesion (2). Since GGO tumor is considered to have a lepidic pattern, which is noninvasive in many cases, a tumor with more GGO content generally has a better prognosis (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%